2022
DOI: 10.3390/ijms232213876
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Genomic and Transcriptomic Elucidation of Flowering in Garlic

Abstract: Commercial cultivars of garlic are sterile, and therefore efficient breeding of this crop is impossible. Recent restoration of garlic fertility has opened new options for seed production and hybridization. Transcriptome catalogs were employed as a basis for garlic genetic studies, and in 2020 the huge genome of garlic was fully sequenced. We provide conjoint genomic and transcriptome analysis of the regulatory network in flowering garlic genotypes. The genome analysis revealed phosphatidylethanolamine-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…Flowering is a key process which indicates the transition from vegetative to reproductive growth for plants, and genes of the PEBP family play important roles during this process and in the final plant architecture [ 3 ]. Up to now, the genes of the PEBP family have been identified in many plant species, such as quinoa, perilla, sugarcane, rice, garlic, etc., and the number of PEBP genes varies among these species [ 41 , 42 , 43 , 44 , 45 ]. A total of 13 PEBP family members were identified in M. integrifolia , and they were classified into three subfamilies: MFT-like , FT-like and TFL1-like .…”
Section: Discussionmentioning
confidence: 99%
“…Flowering is a key process which indicates the transition from vegetative to reproductive growth for plants, and genes of the PEBP family play important roles during this process and in the final plant architecture [ 3 ]. Up to now, the genes of the PEBP family have been identified in many plant species, such as quinoa, perilla, sugarcane, rice, garlic, etc., and the number of PEBP genes varies among these species [ 41 , 42 , 43 , 44 , 45 ]. A total of 13 PEBP family members were identified in M. integrifolia , and they were classified into three subfamilies: MFT-like , FT-like and TFL1-like .…”
Section: Discussionmentioning
confidence: 99%
“…Low temperatures stimulate cascades of developmental mechanisms in several genetic pathways. The transcripts annotated as vernalization genes play a central role in the flowering pathway's interplay [13,35]. Our genome and transcriptome analyses indicate that several variants of VERNALIZATION INSENSITIVE 3 (VIN3), a key gene in temperature perception and plant response to cold [36], are located in garlic chromosomes 3, 4 and 6.…”
Section: Genomic and Transcriptomic Analysis Of Flowering-related Gen...mentioning
confidence: 93%
“…Further morpho-physiological studies showed that in some garlic genotypes, flower initiation and bolting (elongation of flower scape) are completely impaired, while others develop small topsets (bulblets) within the inflorescence which compete with flowers for nutrients. Moreover, even if individual flowers succeed in differentiating, seed production might be compromised by male or female sterility, tapetum degeneration, and pollen abortion [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They further hypothesized that a unique sex determination system exists in these species that differs from Populus and other Salix species. Shemesh-Mayer et al (2022) [ 14 ] presented conjoint genomic and transcriptome analyses of the regulatory network in flowering garlic genotypes and proposed that the process of fertility deprivation in garlic cultivars is based on the loss of the transcriptional functions of the specific genes. Rice and wheat are two of the most important food crops in the world.…”
mentioning
confidence: 99%